Pengaruh Penambahan Kinesiotaping pada Rehabilitasi Pasca Stroke Fase Kronis yang Mendapatkan Weight Shifting Training terhadap Kecepatan Berjalan - Zakaria, Nieke; Handoyo, Rudy; Setiawati, Erna (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: Stroke is the leading cause of disability including decreased walking speed. It is estimated that 73% of stroke sufferers have a lack of motor control and result in limited mobilization. Kinesiotaping(KT) is a method that can be added to other forms of exercise including weight shifting training. With the addition of kinesiotaping is expected to occur improvements in muscle performance and balance so that the speed of walking increases. Objective: To prove the effect of the addition of KT on chronic stroke rehabilitation that gets weight shifting training on walking speed. Methods: This study is a randomized controlled trial pre-test and post test control group design. There were 18 subjects of chronic stroke rehabilitation patients divided into 2 groups, namely the control group that got weight shifting training (9 people) and the treatment group that got the addition of kinesiotaping to weight shifting training (9 people). The walking speed assessment was measured before and after 4 weeks of treatment. Results: There was a significant difference in the mean walking speed before and after treatment in each group (p<0.001). In the treatment group 0.60 ± 0.08 and 0.68 ± 0.07 at the end. In the control group 0.62 ± 0.05 at the beginning and 0.64 ± 0.05 at the end. There was a sigificant difference in the mean walking speed increase in both groups (p<0.001). Conclusion: The mean increased walking speed was higher in the group that got the addition of KT in chronic phase stroke rehabilitation who received weight shifting training.